Lexical Modal Meaning in Grammar Construction - Novan Setiawan Nugraha, Deden (International Journal of Psychosocial Rehabilitation, 2020)
Lexical modality pertains to the speaker’s attitude towards events, which is based on social rules. The social rules can be personal authority (due to age, position, or social status) or authority official (mutually agreed provisions or regulations to regulate the life of the community group concerned). Lexical modal expresses will, desire, or intention of the speaker so that an action is carried out by the interlocutor or the perpetrator. With words, another speaker is authorized to use his authority to make the opponent talk because it is his responsibility. By using descriptive method, this research describes the lexical modal in English modality The data was taken from corpus linguistics, that is, the Corpus of Contemporary American English (COCA).